Responding to the challenge of shortage of personal protective equipment in the corona virus disease 2019 outbreak - Saurabh R Shrivastava; Prateek S Shrivastava (Journal of Dr. NTR University of Health Sciences, 2020)
The Corona Virus Disease-2019 (COVID-19) outbreak, which started from a single city in China in December 2019 has been detected in 53 more nations till 29 February 2020 and this is a significant cause of public health concern worldwide. The available estimates suggest that the use of appropriate personal protective equipment (PPE) in a rational basis is a key component in the prevention and mitigation of the disease. However, amidst loads of uncertainty about various aspects of the disease and the resulting fear and anxiety, the use of PPE has been irrational and thus the public health authorities have faced their shortage and are finding it difficult to ensure optimal availability. In order to deal with the global shortage of PPE, a three-pronged strategy has been proposed focusing on minimizing the need, promoting the rational and appropriate use, and coordinating the supply chain network across the world. In conclusion, the personal protective equipment has an important role in the infection prevention and control of the ongoing COVID-19 outbreak. It is the responsibility of the public health authorities to rationalize the use of PPE to ensure their optimal availability across the world.